OC-034 Outcome Of Patients Considered Unsuitable For Liver Transplantation – A Missed Opportunity For Palliative Care?. (9th June 2014) - Phoolchund, A; Murray, S; Hogan, B; O'Beirne, J
Abstract : Introduction: Patients with end stage liver disease (ESLD) and/or hepato-cellular carcinoma (HCC) may be considered unsuitable for liver transplantation (LT) due to disease severity at presentation or de-listed due to disease progression. These patients have complex medical needs and a limited life expectancy and would be expected to benefit from access to palliative care services. Methods: We performed a retrospective audit of patients assessed for LT between 2010–12 at the Royal Free Hospital. We studied patients who were either not listed at the time of assessment, or listed and subsequently de-listed prior to LT. Sources used included transplant meeting records, hospital notes, local death records and palliative care database. Results: 106 patients were identified. Median age was 58 years (IQR 51–72) and 67% were male. The median MELD score at the time of assessment was 13 (IQR 11–18.75) with a UKELD score of 52 (IQR 49–57). Aetiology of liver disease was divided into Alcohol related Liver Disease (39), Viral (32), Autoimmune (19), Metabolic (8), Cryptogenic cirrhosis (3), other (5). Reasons for not listing included poor clinical state/co-morbidities (48), tumour outside transplant criteria (25), psychosocial/compliance issues (18) and currently too well for LT (15). Excluding patients who were 'Too Well' for LT, Kaplan-Meier Survival analysis calculated the median survival following delisting as 219 days (IQR 28–540). Specifically for those delisted for 'poor clinical state' median survival was 29 days. Overall, 17 (19%) patients were referred to palliative care a median 4 days before death (IQR 2.5–47.5). Conclusion: Those patients who are unfit for LT due to poor clinical state should be referred immediately for palliative care due to limited survival. Patients with HCC outside criteria have a significantly longer survival but still appear to have limited access to palliative care. Liver Transplant programs should have access to dedicated liver palliative care services. Disclosure of Interest: None Declared.